Location Distribution of 2, 087 Osteochondral Lesions of the Talus. (December 2021) - van Diepen, Pascal R.; Dahmen, Jari; Altink, J. Nienke; Stufkens, Sjoerd A.S.; Kerkhoffs, Gino M.M.J.
Objective: The primary aim of this study was to evaluate the exact location distribution in patients with osteochondral lesions of the talus (OLTs) using a 9-grid scheme. The secondary aim is to match lesion location to lesion size, arthroscopic or open operation, and trauma occurrence. Methods: A systematic review was performed in the databases PubMed, EMBASE, and Cochrane. Search terms consisted of "talus" and "osteochondral lesion." Two independent reviewers evaluated search results and conducted the quality assessment using the Methodological Index for Non-Randomized Studies (MINORS). Primary outcome measure was OLT location in the 9 zone-grid. Secondary outcome measures were OLT size in 9-zones, preoperative radiological modality use, demographic lesion size variables as well as open or arthroscopic treatment. Results: Fifty-one articles with 2, 087 OLTs were included. Heterogeneity concerning methodological nature was observed and methodological quality was low. The posteromedial (28%) and centromedial (31%) zones combined as one location was the location with the highest incidence of OLTs with a rate of 59%. Individual OLT size was reported for only 153 lesions (7%). Preoperative combination of X-ray and magnetic resonance imaging (MRI), and/or computed tomography (CT) was reported in 20 studies (43%). Trauma was reported in 78% of patients. Furthermore, 67% was treated arthroscopically and 76% received primary OLT treatment. Conclusion: The majority of OLTs are located in the posteromedial and centromedial zone, while the largest OLTs were reported in the centrocentral zone. Further research is required to identify the prognostic impact of location occurrence on the outcomes following OLT treatment.